Agama dan Etos Kerja: Studi Analisis Terhadap Paham Keagamaan dan Prilaku Ekonomi - Muhammad Yazi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2007)
Religion as an object of scientific research once was debatable because religion is transcendent. The first group argues that religion is an absolute truth; therefore it is not an object of research. Religion is to be believed, not to be reserved about. This is the opinion of religious people. For scientists, religion is an object of research because religion is social and cultural phenomenon. It should be understood that basically religion and humanity has been walking hand in hand in various civilizations. In Islam, it is dialectic between dogmatic teaching of Islam and experience of human being as vicegerent of God on earth. The interaction between the two dimensions always influences the thought about religion across the time. It also concerns the concept of human endeavour vis-a-vis God’s authority. The example are the concepts of Qadariyah, Jabariyah, Mu’tazilah, Asy’ariyah. There are also concepts proposed by social scientists such as Max Weber (Protestant Ethic), David Mc. Clallend (Need for Achievement), and Herman Soewardi (Lemah Karsa or weak initiative).